مستوى البرامج التدريبية لدى مدراء المؤسسات التعليمية - دراسة ميدانية بولاية برج بوعريريج - لفقير, علي; بالقاسمي, محمد الأزهر (University of Eloued جامعة الوادي, 2018)
هدفت الدراسة إلى الكشف عن مستوى البرامج التدريبية لدى مدراء المؤسسات التعليمية وكذا التعرف على دلالة الفروق لدى عينة الدراسة حسب المتغيرات "السن، الأقدمية" في البرامج التدريبية. حيث اعتمدت الدراسة على المنهج الوصفي، وقد تم تصميم استبيان كأداة لجمع البيانات اللازمة، إذ تم توزيعها على عينة مكونة من (127) مديرا "مدير مدرسة ابتدائية، مدير متوسطة، مدير ثانوية " وتم اختيار العينة بطريقة عشوائية بسيطة، وتم تحليل الاستبيان ومعالجته حسب الفرضيات باستخدام الحزمة الإحصائية للعلوم الاجتماعية spss الإصدار رقم (22). وقد توصلت الدراسة إلى النتائج إلى أن مستوى البرامج التدريبية التي استفادة منها مديري المؤسسات التعليمية بولاية برج بوعريريج كان مرتفع في بعدي تنمية المعارف وتنمية الاتجاهات الايجابية بينما كان منخفض في بعد تنمية المهارات، كما توصلت الدراسة إلى عدم وجود فروق ذات دلالة إحصائية في مستوى البرامج التدريبية لدى مدراء المؤسسات التعليمية تعزى لمتغير الأقدمية والسن. Abstract: The study aimed at revealing the level of the training programs of the directors of the educational institutions as well as the significance of the differences in the sample of the study according to the variables "age, seniority" in the training programs. The study was based on a descriptive approach. The questionnaire was designed as a tool for collecting the necessary data. The questionnaire was distributed to a sample of (127) directors, "primary school headmaster, middle school headmaster, secondary school headmaster". The sample was randomly selected, and the questionnaire was analyzed and processed according to the hypotheses using the statistical package for social sciences (SPSS version 22). The study found that the level of training programs benefiting the directors of educational institutions in the state of Bordj Bou Arreridj was high in the development of knowledge and the development of positive trends while it was low in the dimension of skills development, The study also found that there are no statistically significant differences in the level of training programs among managers of educational institutions due to the variable of seniority and age.
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 03 جامعة الوادي
Keywords: البرامج التدريبية